The impact of digital trans transformation on the innovative development of economic systems - Харабара, Віолетта; Obydiennova, Tetiana (My University, 2024)
Taking into account the fact that in the current world, digital technologies are becoming drivers of innovations that affect the economic environment, contributing to the solution of complex problems and the emergence of new opportunities for differentiation, the impact of digital transformation on the innovative development of economic systems is a relevant research. The purpose of the article is to study the impact of digitalization on the innovative development of economic systems in modern conditions, which made it possible to identify the directions of efforts to ensure the innovative development of economic systems in the digitalization conditions. In order to identify the impact of digital transformation on the innovative development of economic systems, this study chose a methodological basis in the form of a systemic approach, which makes it possible to simultaneously take into account general scientific, general economic and applied aspects of the impact of digital transformation on the innovative development of economic systems. The most common problems of innovative development of economic systems are singled out and it is substantiated that it is possible to eliminate their negative impact on innovative development due to the processes of digital transformation. Digitalization tools and their impact on the economic systems’ development are identified, including: cloud technologies, heterogeneous data analytics, artificial intelligence, digital platforms, robotics, virtual and augmented reality. The determinants of the innovative development of economic systems in the digitalization conditions are substantiated. The advantages of the impact of digitalization on the economic systems’ development have been proven. The directions of efforts to ensure the innovative development of economic systems in the digitalization conditions are outlined. The innovative development of economic systems in the digitalization conditions in the form of closed functional dependence is presented.
Keywords: digitization; digital transformation; intellectualization; territorial development; innovative development; economic system; business structures; regional space